Logistic regression analysis to predict parasitism in larvae of Comadia redtenbacheri Hammerschmidt (Lepidoptera: Cossidae) - Zetina, Dulce Azucena; Llanderal-Cázares, Celina; Delos Santos-Posadas, Hector Manuel (ENTOMOTROPICA, 2011)
The agave red worm Comadia redtenbacheri Hammerschmidt. (Lepidoptera: Cossidae), used as food in its larval stage, is a profitable natural resource in Mexico. As part of the quality control required to establish stock for rearing this insect, a risk model using qualitative and quantitative variables was generated to determine the probability of the larvae becoming infested by parasitoids. The variables that were most significant in generating the model were larval weight and position of the lesion on the larvae caused by the parasitoid. There is a greater possibility that a small larva with a ventral or lateral lesion, or with both lesions, is parasitized.